Self- and cross-pollination effects on pollen tube growth and seed set in holm oak Quercus ilex L (Fagaceae) - Yacine, A.; Bouras, F. (Ann. For. Sci., 1997)
Patterns of the self-incompatibility system have been more often described for hermaphroditic, entomophilous and short-lived plant species. Quercus ilex is a long-lived, monoecious, anemophilous and highly self-incompatible species. We used pollination experiments to investigate phenotypic responses of the self-incompatibility system. Flowers from 14 individuals of the same stand were hand-pollinated with self-pollen, cross-pollen from a single donor and a mixture of the two types. We observed a slower pollen tube growth and no or nearly no seed production after self-pollination. The more self-pollen tubes reach the style, the more flowers will stop their ovule development, resulting in a high flower abortion rate. In open pollination, pollen load is not a limiting factor, but incompatible pollen may reach stigma simultaneously or before compatible cross-pollen, which will induce an early abortion of flowers. When pollination is qualitatively and quantitatively effective, the regulation of seed production related to the resources availability acts by the late abortion of fruit.
Keywords: pollen tube growth; Quercus ilex L; seed set; self-incompatibility